Representation of Home: Negotiating Indonesian Identity through Vlogs of Indonesian Women in Transnational Marriage - Safitri Era Globalisasi; Shuri Mariasih Gietty Tambunan (Scriptura, 2024)
As the transnational marriages rise among Indonesians, family vlogs on transnational marriages perform as an indicator of their existence on YouTube. Through daily vlogs, it captures the complexity of transnational family’s life. The mixed culture and identity have become a great challenge for spouses to perform their everyday life, especially for Indonesian woman, who come as a migrant to follow their partners abroad. As a migrant who live in a foreign country, they have to adjust to the environment but as a part of transnational marriage they are carrying a responsibility to pass over both her and her husband’s culture and identity to the family. This paper will examine two YouTube accounts of transnational marriage families which are Kimbab Family and Pita’s Life. Through vlogs, the women negotiate their Indonesian identity in practicing the family. This study uses a textual approach to explain the construction of Indonesian identity in transnational marriages based on their everyday life captured from the vlogs. The result of this research is both Kimbab Family and Pita’s Life representing Indonesian identity through the articulation of nationalism by participating on Indonesian events, vlogs as a ‘translanguaging space’, and finally through food as the articulation of Indonesian diversity. It shows that the identity of transnational marriages are fluid and continues to go through negotiation process.